Use of artificial cells as drug carriers - Emir Diltemiz, Sibel; Tavafoghi, Maryam; De Barros, Natan Roberto [UNESP]; Kanada, Masamitsu; Heinämäki, Jyrki; Contag, Christopher; Seidlits, Stephanie K.; Ashammakhi, Nureddin (Royal Society of Chemistry (RSC), 2021)
Cells are the fundamental functional units of biological systems and mimicking their size, function and complexity is a primary goal in the development of new therapeutic strategies. Recent advances in chemistry, synthetic biology and material science have enabled the development of cell membrane-based drug delivery systems (DDSs), often referred to as artificial cellsor protocells. Artificial cells can be made by removing functions from natural systems in a top-down manner, or assembly from synthetic, organic or inorganic materials, through a bottom-up approach where simple units are integrated to form more complex structures. This review covers the latest advances in the development of artificial cells as DDSs, highlighting how their designs have been inspired by natural cells or cell membranes. Advancement of artificial cell technologies has led to a set of drug carriers with effective and controlled release of a variety of therapeutics for a range of diseases, and with increasing complexity they will have a greater impact on therapeutic designs. This journal is